2019
DOI: 10.1039/c9tb00444k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of formation governs the mechanism of release of antibiotics from calcium phosphate nanopowders and cements in a drug-dependent manner

Abstract: History of formation of the carrier affects the release mechanism, which is drastically dependent on the identity of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
(42 reference statements)
2
13
0
Order By: Relevance
“…Bisso et al used a similar approach for the dual delivery of bisphosphates and nucleic acids [37]. Therapeutic factors can be loaded onto calcium phosphate particles either during the synthesis of the calcium phosphate through co-precipitation [38,39,40] or by combining with the calcium phosphate powders post-synthesis through absorption processes [36]. Co-precipitation can achieve strong chemical interactions between the therapeutic factor and calcium phosphate.…”
Section: Drug and Therapeutic Factor Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Bisso et al used a similar approach for the dual delivery of bisphosphates and nucleic acids [37]. Therapeutic factors can be loaded onto calcium phosphate particles either during the synthesis of the calcium phosphate through co-precipitation [38,39,40] or by combining with the calcium phosphate powders post-synthesis through absorption processes [36]. Co-precipitation can achieve strong chemical interactions between the therapeutic factor and calcium phosphate.…”
Section: Drug and Therapeutic Factor Deliverymentioning
confidence: 99%
“…The interactions that occur vary depending on the antibiotic used. For example, Uskoković successfully combined vancomycin and ciprofloxacin with both amorphous and crystalline HA nanoparticles and found that vancomycin was released more when amorphous powders were used, whereas ciprofloxacin was released more quickly when using the crystalline powders [40]. Gbureck et al demonstrated that vancomycin and ofloxacin created only weak bonds with calcium phosphate nanoparticles and reported that the absorption of these antibiotics was dependent on their specific surface area and not composition [49].…”
Section: Drug and Therapeutic Factor Deliverymentioning
confidence: 99%
“…The insulin proxy release profiles were also analyzed for the mechanism of release based on the fits with the Korsmeyer–Peppas kinetic model. For the release from MnO 2 @PCL films, regardless of the concentration of glucose in the medium, the release mechanism, given the value of the Korsmeyer–Peppas exponent being higher than 1 ( Figure 5 a), was classified as non-Fickian super case II diffusion [ 59 ]. This type of diffusion defies Fick’s law owing to a nonlinear function of the mean squared displacement versus time and applies to a case where the diffusion is very fast compared with the polymer chain relaxation rate [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Explanations given by the authors referred to a number of thermodynamic considerations, such as the surface energy and solubility of precursor powders with respect to their crystalline or amorphous conditions. The follow-up article from 2019 [ 39 ] focused on elucidating the characteristics of this mechanism of drug release in the same system of cements comprising HAp1 and HAp2 at different proportions. Basic considerations for the investigated cements were the same as in the previously described work [ 38 ].…”
Section: General Matrix Featuresmentioning
confidence: 99%
“…The initial rate was higher for vancomycin and this was explained in terms of the water solubility of vancomycin, which is 10-fold higher than that for ciprofloxacin. Another comparison between vancomycin and ciprofloxacin was performed in an experiment described in two works by the group of Uskoković [ 38 , 39 ]. In these works, both drugs were loaded inside different CPC matrices, indicated as HAp1, HAp2 and their combinations at different ratios, namely 85:15 HAp1:HAp2 and 50:50 HAp1:HAp2.…”
Section: Drug Typementioning
confidence: 99%